Pengembangan E-LKPD Interaktif Berbasis PBL Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Materi Trigonometri Kelas X - Sari, Ni Kadek Ayu Indah; Suharta, I Gusti Putu; Parwati, Ni Nyoman (Universitas Negeri Malang, 2025)
The purpose of this written research is to identify the features of interactive E-LKPD based on problem-based learning that have valid, practical, and effective properties in improving the mathematical problem solving ability of high school students in grade X on trigonometry material. The ADDIE development model is applied in the development of interactive E-LKPD through the utilization of the Liveworksheet website. The practicality test is carried out using UEQ (User Experience Questionnaire), the validity and suitability test of the media is carried out using the LORI assessment questionnaire, and the effectiveness test is carried out by assessing the completeness of the problem-solving ability test. The validity test of the material and the feasibility of the media uses the LORI assessment questionnaire, the practicality test of the material uses the UEQ , and the effectiveness test uses the completeness of the problem-solving ability test. The feasibility test of the material with very strict requirements. The feasibility test of the media has very high standards. The very good criteria for the practicality test are given to teachers and students of grade X of SMA Negeri 1 Tabanan including questionnaires in each area. The effectiveness of the interactive E-LKPD developed is very good, based on the effectiveness test. Abstrak Tujuan penelitian tertulis untuk mengidentifikasi fitur-fitur E-LKPD interaktif berbasis problem based learning dengan memiliki sifat-sifat valid, praktis, serta efektif dalam meningkatkan sebuah kemampuan pemecahan masalah matematika siswa SMA kelas X pada materi trigonometri. Model pengembangan ADDIE diterapkan dalam pengembangan E-LKPD interaktif melalui pemanfaatan website Liveworksheet. Uji praktikalitas dilaksanakan dengan menggunakan UEQ (User Experience Questionnaire), uji validitas serta kesesuaian pada media dilaksanakan dengan menggunakan angket asesmen LORI, dan uji efektivitas dilaksanakan dengan menilai kelengkapan tes kemampuan pemecahan masalah. Uji validitas materi serta kelayakan media menggunakan angket penilaian LORI, uji kepraktisan materi menggunakan UEQ, serta uji keefektifan menggunakan ketuntasan tes kemampuan pemecahan suatu masalah. Uji kelayakan materi dengan persyaratan yang sangat ketat. Uji kelayakan media memiliki standar yang sangat tinggi. Kriteria sangat baik pada uji kepraktisan diberikan pada guru dengan siswa kelas X SMA Negeri 1 Tabanan meliputi angket disetiap area. Keefektifan E-LKPD interaktif yang dikembangkan sangat baik, berdasarkan uji keefektifan